The Association Between Gestational Diabetes and Microbiota in Placenta and Cord Blood - Tang, Ning; Luo, Zhong-Cheng; Zhang, Lin; Zheng, Tao; Fan, Pianpian; Tao, Yexuan; Ouyang, Fengxiu (Frontiers in Endocrinology, 2020)
Objective: Early life is a critical period for gut microbial development. It is still controversial whether there is microbiota during a healthy pregnancy. Gestational diabetes mellitus (GDM) is associated with increased risk of metabolic syndrome in the offspring and the mechanisms are unclear. We sought to explore whether microbiota in placenta and cord blood may be altered in GDM. Methods: Placenta and cord blood samples were collected from 8 GDM and 7 euglycemic (control) term pregnancies in caesarean deliveries without evidence of clinical infections. The Illumina MiSeq Sequencing System was used to detect the microbiota based on the V3-V4 hypervariable regions of the 16S ribosomal RNA gene. Results: The microbiota were detectable in all placental samples. Compared GDM vs. controls, there were more operational taxonomic units (OTUs) (Mean±SE: 373.63±14.61 versus 332.43±9.92, P=0.024), higher Ace indice (395.15±10.56 versus 356.27±8.47, P=0.029) and Chao indice (397.67±10.24 versus 361.32±8.87, P=0.04). The placental microbiota was mainly composed of four phyla: Bacteroidetes, Firmicutes, Actinobacteria, Proteobacteria at the phylum level and 10 dominant genus at the genus level in both GDM and controls. Despite of the dominant similarity in microbiota composition, at the OTU level, the abundance of Ruminococcus, Coprococcus, Paraprevotella, and Lactobacillus were higher, while Veillonella was lower in the placentas of GDM vs. controls. The microbiota was detected in one of the 15 cord blood samples, and its components were similar as to the corresponding placental microbiota at both phylum and genus levels suggesting placental microbiota as the potential source. Conclusions: The most abundant phyla and genus of placental microbiota were similar in GDM and euglycemic pregnancies, but GDM was associated with higher diversity of placental microbiota. Further study is needed to confirm the existence of microbiota in cord blood in pregnancies without clinical infection.